Tumour-associated neutrophils secrete AGR2 to promote colorectal cancer metastasis via its receptor CD98hc–xCT. Issue 12 (27th January 2022) - Tian, Shaobo; Chu, Yanan; Hu, Jia; Ding, Xueliang; Liu, Zhibo; Fu, Daan; Yuan, Ye; Deng, Yan; Wang, Guobin; Wang, Lin; Wang, Zheng
Abstract : Objective: Reciprocal cellular crosstalk within the tumour microenvironment (TME) actively participates in tumour progression. The anterior gradient-2 (AGR2) can be secreted to extracellular compartments and contribute to colorectal cancer (CRC) metastasis. We investigated the cellular source for secreted AGR2 in the TME and underlying mechanisms mediating secreted AGR2's effects. Design: Tissue microarray, tumour tissues, blood samples and tumour-associated neutrophils (TANs) from patients with CRC were isolated for phenotypical and functional analyses. The role of TAN-secreted AGR2 was determined in neutrophil-specific Agr2 knockout ( Agr2 f/f ;Mrp-Cre ) mice. The biological roles and mechanisms of secreted AGR2 in CRC metastasis were determined in vitro and in vivo. Results: TANs were a predominant cell type for secreting AGR2 in the TME of CRC. TANs-secreted AGR2 promoted CRC cells' migration. Neutrophils-specific ablation of Agr2 in mice ameliorated CRC liver metastases. The heavy chain of CD98 (CD98hc) served as the functional receptor for secreted AGR2. Mechanistically, secreted AGR2 increased xCT activity in a CD98hc-dependent manner, subsequently activating Ras homologue family member A/Rho-associated protein kinase 2 cascade. CRC cells actively recruited TANs through the C-X-C motif chemokine 2. Moreover, CRC-derived transforming growth factor beta 1 (TGF-β1) educated peripheral blood neutrophils to become AGR2 + TANs that secrete AGR2. Abundant infiltration of AGR2 + TANs and high expression of TGF-β1 and CD98hc–xCT were correlated with poor prognosis of patients with CRC. Conclusions: Our study unveils a novel crosstalk between TANs and CRC cells involving the secreted AGR2–CD98hc–xCT axis that promotes metastasis and impacts the outcomes of patients with CRC.